Strategi Komisi E DPRD Sumut dalam Menjalankan Fungsi Pengawasan Pembangunan Dan Kesejahteraan Sosial di Sumatera Utara - Melky, Martin; Lubis, Yurial Arief; Lubis, Khairunissah (Universitas Medan Area, 2024)
This article or writing aims to analyze the North Sumatra DPRD Commission E Strategy (Period 2019-2024) in measuring the Development Supervision and Social Welfare Function in North Sumatra Province and analyze the Inhibiting Factors of the North Sumatra DPRD Commission E Strategy (2019-2024 Period) in carrying out the Development Supervision Function And Social Welfare in North Sumatra Province. Data was collected through interviews, observation, and documentation and analyzed qualitatively. This study concludes that the North Sumatra DPRD Strategy Commission E (2019-2024) in monitoring development and social welfare includes planning strategies, the use of competent human resources, and budget efficiency. However, limited human resources, absence of members at meetings, and lack of understanding of regulations hamper its effectiveness. To increase effectiveness, it is necessary to increase human resource capacity, ensure meeting attendance, and better understand the regulations. Overcoming these obstacles will strengthen Commission E's supervisory function and increase its contribution to development and social welfare in North Sumatra Province.